Droplet Regulation and Dropwise Condensation Heat Transfer Enhancement on Hydrophobic-Superhydrophobic Hybrid Surfaces. Issue 17 (8th November 2018) - Lan, Zhong; Chen, Yansong; Hu, Shaobo; Yin, Guangzhao; Ma, Xuehu
ABSTRACT: Efficient Dropwise condensation on nanostructured superhydrophobic surfaces (SHS) has received extensive attention. However, good heat performance only occurs in two conditions: the presence of non-condensable gas, or low surface subcooling. For industrial pure steam condensation, large droplets tend to be pinned on the surfaces due to the large contact angle hysteresis (CAH) and impede heat transfer process. In this study, the SHSs and hydrophobic surface (HS) were integrated in spaced band pattern with different width and CAH. It was observed that the condensed droplets experience a fast horizontal shifting from hydrophobic zones to superhydrophobic zones driven by adhesive force. In this way, the departure path of droplets were altered and the refreshing frequencies are increased for both SHS and HS regions. The heat transfer coefficients for some 1 mm × 1 mm hybrid surfaces were found to be elevated by about 25% at subcooling of 6K compared to the weighted mean value of individual HSs and SHSs. For surfaces with short dividing distance (about 0.5 mm × 0.5 mm), the bridging effects between droplets in SHS regions were also observed, which is undesirable for heat transfer. These work indicates that strong adhesive force of SHSs can function as a promoter of droplet condensation for hybrid surfaces with proper choice of dividing width.